1373. Using Geospatial Analysis to Describe the Association between Active Tick Surveillance Data and Clinical Cases of Anaplasmosis. (15th December 2022) - Desiato, Julia T; Banach, David; Chan, Grace; Palmeri, Marco
Abstract: Background: Anaplasmosis is a vector-borne disease spread by Ixodes scapularis ticks mainly in the Northeastern United States. The Connecticut Department of Public Health (CT DPH) made anaplasmosis a state-wide reportable disease in 2008 and a large increase in reportable cases was seen in Connecticut between 2014 and 2019. Methods: This study used clinical cases of anaplasmosis reported to the CT DPH and tick infection prevalence data to understand emerging geographic hotspots for the disease in the state and to evaluate the association between the human and tick infections. Human incidence rates (IR) were calculated per 100, 000 in the population by county. Tick infection prevalence was calculated as an acarological risk index (ARI) using active tick surveillance data from the Connecticut Agricultural Experiment Station (CAES). These two calculations were analyzed with a Spearman rank correlation in SAS version 9.4 and overlaid on ArcMap. Results: During the 2019-2020 period, 420 human cases of anaplasmosis were included and 148 infected ticks were identified. There was a significant positive correlation between IR and ARI identified (Spearman correlation 0.54, p = 0.03). Litchfield County had the highest number of human cases (128) and Fairfield County had the highest proportion of infected ticks (11.25%). The area with the greatest increase in both ARI and IR in Connecticut from 2019-2020 was New London County (ARI increased from 0.073 to 0.108, IR increased from 2.64 to 8.57). Conclusion: This study supports the use of active tick surveillance in identifying geographic areas high incidence of human anaplasmosis and provides a strategy to evaluate tick surveillance for anaplasma infection. Active tick surveillance can be useful in guiding public health interventions and inform public health and clinician education on anaplasmosis. Disclosures: All Authors : No reported disclosures.